Comparison of rRNA-based reverse transcription PCR and rDNA-based PCR for the detection of streptococci in root canal infections - Laís Cunha PRADO; Giulio GAVINI; Amanda da Costa SILVEIRA; Vitor Cesar NAKAMURA; Marcia Pinto Alves MAYER; Ericka Tavares PINHEIRO
Abstract Objective The rDNA-based method is unable to distinguish between alive and dead cells. Alternatively, bacterial viability can be assessed by molecular methods based on ribosomal RNA (rRNA). Therefore, this study aimed to detect viable streptococci in root canal samples using rRNA-based reverse transcription polymerase chain reaction (RT-PCR), compared to an rDNA-based PCR assay. Methodology Microbiological root canal samples were obtained from 32 teeth with primary endodontic infections before (S1) and after chemomechanical preparation (S2), and after removal of intracanal medication (S3). RNA and DNA were extracted, and complementary DNA (cDNA) was synthesized from RNA using RT reaction. cDNA and genomic DNA were subjected to PCR with primers complementary to the 16S rRNA sequences of Streptococcus spp. McNemar's test was used to compare the detection rate of both assays (P<0.05). Results Streptococci were detected in 28.12% (9/32) and 37.5% (12/32) of S1 samples using rRNA- and rDNA-based PCR assays, respectively. In contrast, they were detected in only 6.25% (2/32) of S2 samples using rRNA-based RT-PCR, compared to 15.62% (5/32) using rDNA-based PCR. Finally, in S3 samples, streptococci were not detected by rRNA, whereas rDNA-based PCR still detected the bacteria in 12.5% (4/32) of the samples. The total number of PCR-positive reactions in the rDNA-based PCR was higher than in the rRNA-based assay (P<0.05). Conclusions The rRNA-based RT-PCR showed a lower detection rate of streptococci when compared to the rDNA-based PCR, suggesting that the latter may have detected dead cells of streptococci in root canal samples.